The relationship between hypertension, anemia, and BMI in women of reproductive age: evidence from a nationwide health study - Shiva Raj Acharya; Diwash Timilsina; Sandip Pahari; Sabitri Acharya; Navin Ray (BMC Cardiovascular Disorders)
Abstract Background Hypertension, anemia, and malnutrition are significant global health challenges. While prior studies have primarily focused on the prevalence of these conditions in Nepal, no research has investigated the interrelationship among them. Therefore, this study aimed to investigate the association of hypertension with anemia, blood hemoglobin levels, and body mass index (BMI) among women of reproductive age. Methods Using multilevel logistic regression models, we analyzed nationally representative data from the 2022 Nepal Demographic and Health Survey (NDHS). A total of 4,133 eligible women aged 15–49 were included in this study. Hypertension (systolic pressure ≥ 140 mmHg or diastolic pressure ≥ 90 mmHg), anemia (blood hemoglobin < 12 g/dl), and BMI categories were defined according to the World Health Organization (WHO) guideline. Student’s t-test, Pearson’s Chi-square, and linear regression analysis were performed in the analysis. Results The mean age of the participants was 29.78 ± 9.61 years. The prevalence of hypertension was significantly higher in women without anemia than those with anemia (9.0% vs. 5.4%, p < 0.001). An inverse association was observed between hypertension and anemia (OR, 0.73; 95% CI: 0.55–0.96; p < 0.01). Increased hemoglobin levels (systolic: β, 1.24; 95% CI: 0.14–1.46; diastolic: β = 1.57, 95% CI: 1.38–1.71) and BMI (systolic: β = 0.89, 95% CI: 0.80–0.99; diastolic: β = 0.84, 95% CI: 0.68–0.92) were positively correlated with hypertension. Smoking, overweight, obesity, and increased mid-upper arm circumference (MUAC) were found to increase the risk of hypertension. Conclusion This study demonstrates a positive association between hypertension and BMI, while anemia was linked to a lower risk of hypertension. The findings suggest that higher hemoglobin levels may serve as an independent risk factor for hypertension. Therefore, regular screening of hemoglobin levels and BMI, along with interventions addressing dietary and lifestyle factors is recommended to mitigate the risk of hypertension.